Kawasaki disease and ENSO‐driven wind circulation. Issue 10 (29th May 2013) - Ballester, Joan; Burns, Jane C.; Cayan, Dan; Nakamura, Yosikazu; Uehara, Ritei; Rodó, Xavier
Abstract [1] Kawasaki disease (KD) is the most common cause of acquired heart disease in children worldwide. Recently, a climatological study suggested that KD may be triggered by a windborne agent traveling across the north Pacific through the westerly wind flow prevailing at midlatitudes. Here we use KD records to describe the association between enhanced disease activity on opposite sides of the basin and different phases of the El Niño‐Southern Oscillation (ENSO) phenomenon, via the linkage to these tropospheric winds. Results show that years with higher‐than‐normal KD cases in Japan preferentially occur during either El Niño Modoki or La Niña conditions, while in San Diego during the mature phase of El Niño or La Niña events. Given that ENSO offers a degree of predictability at lead times of 6 months, these modulations suggest that seasonal predictions of KD could be used to alert clinicians to periods of increased disease activity.